EXPERIMENTAL INVESTIGATION AND MODELING OF MODIFICATION AGENT ON SURFACE PROPERTY OF AEROGEL PRODUCED VIA AMBIENT PRESSURE DRYING - Al-Sharuee, Israa F (MATTER: International Journal of Science and Technology, 2019)
A crucial properties for hydrophobic silica aerogels such as surface free energy surface tension contact angle has been determines experimentally and theoretically in the present work, the modification was by hexamethyldisilazane (HMDZ) and trimethylchlorosilane (TMCS) with different concentration from 5% to 15% , two step acid base catalysis followed in preparation, using (TEOS) ethanol and [0.001M] hydrochloride acid with molar ratio was 1:2.8:0.19*10-3 respectively , the effect study upon analysis of FTIR spectra and the degree of hydrophobicity was estimated by contact angle measurements. The results refer that the contact angle of aerogel from 130 to 151 by modifying by HMDZ and from 122 to 153 by modifying by TMCS, Neumann’s and Young’s equation of state depend to determine surface free energy and surface tension of samples, while the specific surface area is measured by using the "Brunauer –Emmett–Teller (BET) method. Here, we have confirmed that the surface free energy of samples can be regulated in varied range from 4.4997 to 0.3115 and 4.1419 to 0.5112 mJ/m2 by adjusting their surface by TMCS and HMDZ. From results the modification with TMCS is best from HMDZ, theoretical part give a good results to estimate the important information about hydrophobic silica aerogel.